Lying to an older adult in a sharing situation: differences between young and mid-life adults - Elaad, Eitan; Bracha, Yakir; Avraham, Hodaya; Rabi, Chen; Katzin, Talya (Frontiers in Psychology, 2025)
IntroductionThe present study aimed to demonstrate lying to older adults by young and mid-life participants in the Ultimatum Game (UG). Another goal was to reexamine the Self-Reported Lying Scale (SRLS), validate the short Hebrew version of the need for cognition scale (NCS-6), and show how they predict lying in the present experimental conditions.MethodsWe allocated 379 examinees (196 women) to six experimental conditions in a 2 × 3 factorial design. Two participant’s age conditions (young and middle-aged) and three receiver’s age conditions (25, 50, and 70 years). Participants underwent a UG where they were permitted to conceal part of the endowment from the receiving woman. They then shared the remaining money with the receiver. Finally, participants completed the SRLS and the NCS-6.ResultsParticipants (mainly young) tended to evaluate an older woman less favorably than younger versions of that woman. Young participants concealed more of their endowment than mid-life participants. Young participants were more generous than their mid-life counterparts when sharing the remaining endowment with the older woman. Hiding a more significant part of the endowment while offering a fairer share of the remaining award (Fake Fairness) was observed for young participants. Fake Fairness to the older woman by younger participants was more significant than the receiver’s younger variations. The SRLS global score and four subscales predicted participants’ lying in the UG. NCS-6 prediction of lying was also significant, although less efficient than the SRLS.DiscussionThe present study aimed to examine ageism by lying to an older woman in the UG. Indeed, young participants lied more to an older receiver than to younger versions of that receiver, whereas mid-life participants did not. We suggest that mid-life participants prepare themselves psychologically to join an older community and, therefore, are more tolerant toward older people than their younger counterparts. Young participants scored higher on the SRLS and lied more in the UG than mid-life participants. The present study contributes to a better understanding of the different approaches to lying by young and mid-life people. Young participants were relatively free to consider lying and behaving deceptively, whereas mid-life participants restricted their lying behavior and attitudes toward lying.